PM2.5 exposure during pregnancy induces hypermethylation of estrogen receptor promoter region in rat uterus and declines offspring birth weights. (December 2018) - Dang, Shaokang; Ding, Ding; Lu, Yong; Su, Qian; Lin, Tianwei; Zhang, Xiaoxiao; Zhang, Huiping; Wang, Xuebin; Tan, Houzhang; Zhu, Zhongliang; Li, Hui
Abstract: Particulate matter 2.5 (PM2.5 ) exposures during pregnancy could lead to declined birth weight, intrauterine developmental restriction, and premature delivery, however, the underlying mechanisms are still not elucidated. There are few studies concerning the effects of PM2.5 exposure on maternal and child health in Xi'an (one of the cities with severe air pollution of PM2.5 in North China). Then, this study aimed to investigate the effect of PM2.5 exposure in Xi'an on the offspring birth weights and the possibly associated epigenetic mechanisms. We found the Low and High groups: the offspring with declined birth weights; the decreased mRNA and protein expression of the estrogen receptor (ERs) and eNOs in the uterus; the decreased endometria vascular diameter maximum (EVDM); the increased mRNA and protein expressions of the DNMT1 and 3b in the uterus; the elevated methylation levels of the CpG sites in the CpG island of ERα promoter region in the uterus. However, no differences were observed in the mRNA or protein expressions of ERβ and DNMT3a between the Clean and PM2.5 exposure groups, as well as endometriavascular density (EVD). Additionally, PM2.5 level was negatively correlated with the ERα protein expression, EVDM and offspring birth weight, as well as the methylation level of the CpG sites in the CpG island of ERα promoter region and the ERα protein expression in the uterus; whereas the ERα protein expression was positively correlated with the offspring birth weight, as well as PM2.5 level and the methylation level of the CpG sites in the CpG island of ERα promoter region in the uterus. Taken together, elevated methylation level of the CpG sites in the CpG island of ERα promoter region reduces ERα expression in the uterus, which could be one of the epigenetic mechanisms that pregnant PM2.5 exposure reduces the offspring birth weights. Graphical abstract: Image 1 Highlights: PM2.5 exposure during pregnancy induced methylation of ERα promter in uterine. Elevated methylation reduced the expression of ERα in the uterus. PM2.5 exposure during pregnancy reduced the expression of eNOs in the uterus. PM2.5 exposure reduced blood flow of intrauterine fetal rats via ERα-eNOs. Offspring birth weights were decreased afterPM2.5 exposure. Abstract : PM2.5 exposure during pregnancy induces hypermethylation of the CpG sites in CpG island of ERα promoter region to in rat uterus and then contributes to the reduction of offspring birth weights.